Implementation of the Application of Multi Akad Murabahah and Rahn in the Mulia Metal Products in the Sharia Pawnshops City of Singkawang Islamic Law Perspective - Zarul Arifin; Hatoli Hatoli (IAIN Manado, 2021)
The juridical operation of any sharia-based financial institution must refer to the DSN-MUI fatwa, including the multi-contract issue or better known as a hybrid contract, where has mandated by Law No. 21 of 2008 concerning Islamic Banking Article 26 paragraph (2). Two multi-contracts are permitted by the DSN-MUI in the fatwa, namely Fatwa No. 71 of 2008 concerning Sale and Lease Back and Fatwa No. 72 Years. 2008 on Ijarah Sale and Back. However, PT. Pegadaian (Persero) Alianyang Singkawang Sharia Service Unit has carried out multiple contracts (murabahah and Rahn) since the last 6 (six) years on Murabahah Logam Mulia Abadi Investment (MULIA) products for non-cash Financing of gold. There is no fatwa from DSN- MUI, so that raises doubts about the guarantee of the quality of the product. So it is essential to study how the MULIA product contract system uses the murabahah and Rahn contracts from the perspective of sharia economic law. This research is descriptive qualitative research that deepens by conducting direct interviews with the parties involved in implementing multi-murabahah and Rahn contracts. This research completed in 2019. The sources of data in this study are the leadership and staff at the Singkawang sharia pawnshop, then customers who use multi-contract product services at the Singkawang sharia pawnshop. The results of the study concluded that the application of multi-murabahah and Rahn contracts on precious metal products at PT. Pegadaian (Persero) Alianyang Singkawang Sharia Service Unit, as stipulated in Law No. 21 of 2008 concerning sharia banking, has been implemented on this product. Therefore, in the view of sharia economic law, it is permissible and justified because the system refers to the DSN-MUI fatwa No. 92 of 2014 concerning Financing that accompanied by Rahn and becomes the basis for the use of multiple contracts.